Combined cognitive–behavioural and mindfulness programme for people living with dystonia: a proof-of-concept study. Issue 8 (5th August 2016) - Sandhu, H; Bernstein, C J; Davies, G; Tang, N K Y; Belhag, M; Tingle, A; Field, M; Foss, J; Lindahl, A; Underwood, M; Ellard, D R
Abstract : Objectives: To design and test the delivery of an intervention targeting the non-motor symptoms of dystonia and pilot key health and well-being questionnaires in this population. Design: A proof-of-concept study to test the delivery, acceptability, relevance, structure and content for a 3-day group residential programme for the management of dystonia. Setting: Participants were recruited from a single botulinum toxin clinic. The intervention was delivered in the community. Participants: 14 participants consented to take part (2 withdrew prior to the starting of intervention). The average age was 60 years (range 44–77), 8 of whom were female. After drop-out, 9 participants completed the 3-day programme. Intervention: A 3-day group residential programme. Primary and secondary outcome measures: Process evaluation and interviews were carried out before and after the intervention to explore participant's views and expectations, as well as experiences of the intervention. Select questionnaires were completed at baseline, 1-month and 3-month follow-up. Results: Although participants were not sure what to expect from the programme, they found it informative and for many this together with being in a group with other people with dystonia legitimised their condition. Mindfulness was accepted and adopted as a coping strategy. This was reflected in the 1-month follow-up. Conclusions: We successfully delivered a 3-day residential programme to help those living with dystonia manage their condition. Further improvements are suggested. The quantitative outcome measures were acceptable to this group of patients with dystonia.